Characteristics, Associated Diseases, and Management of Gramnegative Toe-web Infection: A French Experience - Anne Goiset; Brigitte Milpied; Aurélie Marti; Jérome Marie; Vaianu Leroy-Colavolpe; Anne Pham-Ledard; Olivier Chosidow; Marie Beylot-Barry (Medical Journals Sweden, 2019)
Gram-negative toe-web infection can cause pain and disability, be complicated by a long healing time, management failure, and cellulitis, and recur due to persistent predisposing factors. To describe the clinical features and management of Gram-negative toe-web infection and evaluate predisposing factors and associated diseases, their management, and the effect of controlling them on the rate of recurrence, we conducted a retrospective real-life study of patients with Gram-negative toe-web infection. Among the 62 patients (sex ratio 9:1), 31 experienced more than one episode of Gram-negative toe-web infection. Pseudomonas aeruginosa was the most prominent bacteria. Predisposing factors/associated diseases were eczema (66%), suspected Tinea pedis (58%), humidity (42%), hyperhidrosis (16%), psoriasis (11%), and vascular disorders (40%). Patients in whom associated diseases, such as eczema or psoriasis, were controlled did not relapse, suggesting the benefit of management of such conditions. We suggest that management of Gram-negative toe-web infection be standardised, with a focus on diagnosis and treatment of associated diseases.